Agricultural plant jiaosu: valorization of organic wastes for sustainable agriculture - Wang, Yumeng; Li, Jianxun; Li, Xin; Wu, Shankai; Song, Wenjun; Li, Ping (Frontiers in Sustainable Food Systems, 2024)
Agricultural plant jiaosu (APJ) represents a novel and highly valuable ecological input with multiple applications. It is utilized as foliar fertilizer, drip irrigation fertilizer, bio-pesticide, and decomposing fungicide, facilitating the enrichment of local beneficial microorganisms and the efficient treatment of local organic waste. The technology offers the advantages of straightforward operation, minimal equipment requirements, and low cost. Its potential applications and research areas are extensive, with benefits including enhanced plant growth, improved crop quality, soil ecology enhancement, reduced environmental pollution, and prevention of crop pests and diseases. Despite its potential, there is a shortage of review papers on APJ in agricultural practices. This essay aims to provide an overview of the concept, categorization, preparation methods, and primary ingredients of APJ. It also discusses the impacts of APJ on agro-ecological systems and reviews current research, focusing on aspects such as raw material selection, microbial fermentation, the fermentation process, and detection technologies. However, further investigation and study are necessary due to the complex composition of APJ.